“You knew you had to be there, it had to be done”: Experiences of health professionals who faced the COVID-19 pandemic in one public hospital in Spain - Rodríguez-Madrid, María Nieves; Pastor-Moreno, Guadalupe; Albert-Lopez, Enrique; Pastor-Valero, María (Frontiers in Public Health, 2023)
Introduction The COVID-19 pandemic highlighted the lack of a government contingency plan for an effective response to an unexpected health crisis. This study uses a phenomenological approach to explore the experience of healthcare professionals during the first three waves of the COVID-19 pandemic in a public health hospital in the Valencia region, Spain. It assesses the impact on their health, coping strategies, institutional support, organizational changes, quality of care, and lessons learned. Methods We carried out a qualitative study with semi-structured interviews with doctors and nurses from the Preventive Medicine, Emergency, and Internal Medicine Services and the Intensive Care Unit, using the Colaizzi’s 7-step data analysis method. Results During the first wave, lack of information and leadership led to feelings of uncertainty, fear of infection, and transmission to family members. Continuous organizational changes and lack of material and human resources brought limited results. The lack of space to accommodate patients, along with insufficient training in treating critical patients, and the frequent moving around of healthcare workers, reduced the quality of care. Despite the high levels of emotional stress reported, no sick leave was taken; the high levels of commitment and professional vocation helped in adapting to the intense work rhythms. Healthcare professionals in the medical services and support units reported higher levels of stress, and a greater sense of neglect by their institution than their colleagues in managerial roles. Family, social support, and camaraderie at work were effective coping strategies. Health professionals showed a strong collective spirit and sense of solidarity. This helped them cope with the additional stress and workload that accompanied the pandemic. Conclusion In the wake of this experience, they highlight the need for a contingency plan adapted to each organizational context. Such a plan should include psychological counseling and continuous training in critical patient care. Above all, it needs to take advantage of the hard-won knowledge born of the COVID-19 pandemic.